1994
DOI: 10.1080/08838159409364268
|View full text |Cite
|
Sign up to set email alerts
|

A content analysis of gender differences in children's advertising

Abstract: This content analysis of children's advertising examined the differences between television advertisements featuring only one sex of actors. The advertisements that were studied aired during a week of after-school and Saturday morning children's programming. Advertisers featured more boys than girls and placed boys in settings outside their homes more often. The sex of announcers corresponded to the sex of the characters in the ads. Overall, the advertisements exhibited stereotyped behavior for traditional sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
5

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 18 publications
(36 reference statements)
3
60
0
5
Order By: Relevance
“…While an expansive amount of research has been published on children's media, previous research tends to look more at children's media in general, across several networks (e.g., broadcast and cable combined) or at the "fads of the day"-shows that come and go with a whirlwind of attention surrounding them (Hendershot 2004;Johnson and Young 2002;Maher and Childs 2003;Larson 2001;Smith 1994).…”
Section: Toys and Gender-role Expectanciesmentioning
confidence: 98%
“…While an expansive amount of research has been published on children's media, previous research tends to look more at children's media in general, across several networks (e.g., broadcast and cable combined) or at the "fads of the day"-shows that come and go with a whirlwind of attention surrounding them (Hendershot 2004;Johnson and Young 2002;Maher and Childs 2003;Larson 2001;Smith 1994).…”
Section: Toys and Gender-role Expectanciesmentioning
confidence: 98%
“…Smith (1994) analyzed ads aired on children's programming in 1991 and found ads featuring only one sex or the other to be sex-role stereotypical. He concluded that when "advertisements only show traditional sex roles, they limit the range of experiences that children can try out" (p. 335).…”
Section: Gender Codes In Children's Advertisingmentioning
confidence: 99%
“…Activities portrayed in commercials often signify traditional gender roles. For example, Smith (1994) observed that girls engaged in shopping, whereas boys did not, and that only boys performed antisocial behaviors, such as stealing or fighting. Aggressive behavior seems to be more visible in commercials that feature boys than in those that feature girls (Larson, 2001;Macklin & Kolbe, 1984;Welch, Huston-Stein, Wright, & Plehal, 1979).…”
Section: Depictions Of Gender In Children's Television Commercialsmentioning
confidence: 95%
“…Early research indicated that boys' commercials were more likely to contain highly active toys, higher rates of cuts, more rough cuts, less talking, and louder noise and music than girls' commercials, which had more fades and dissolves, smoother transitions, a great deal of talking, and softer background music (Welch et al, 1979). Research in the 1990s suggested that voice-overs were used to match the orientation of the target for the toy such that boy-oriented commercials featured a male voiceover and girloriented commercials featured a female voiceover (Johnson & Young, 2002;Smith, 1994). These factors tend to serve as signifiers of appropriate gendered behavior and toy selection.…”
Section: Depictions Of Gender In Children's Television Commercialsmentioning
confidence: 97%